The Role of Machine Translation in Modern Communication - Bozorova Vasila Ilhom qizi (Peerian Journals Publishing, 2024)
In our interconnected world, people from diverse backgrounds frequently communicate with one another. However, language differences remain a significant barrier. Machine translation (MT) helps to bridge this gap by enabling people to translate text or speech between languages. This article explores how machine translation works, its benefits, challenges, and its role in shaping communication in the future.
Keywords: Machine translation; method; deep learning; machine translation technology